Interview with Silvia Federici - Moreno, Esther (Filanderas, 2017)
In September 2017, Silvia Federici gave two lectures in Zaragoza: «Marxism and feminism», at the University of Zaragoza, invited by the VI International Meeting of Young Researchers in Contemporary History; and «Capitalism and Violence against Women», at the Luis Buñuel Social and Community Center, organized by Nociones Comunes and Traficantes de Sueños.